Proton Momentum Distributions in Strong Hydrogen Bonds in the Solid State - Matthew Krzystyniak; Felix Fernandez-Alonso (Proceedings, 2019)
Neutron Compton scattering (NCS) is a unique experimental technique made possible by the [...]